The effect of problem based learning model on learning outcomes in the vocational high school students - Aslam, Lera Kurniatul; Suparji, Suparji; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2021)
The main problem in formal learning is that teachers carry out learning with direct learning models and lectures. The right learning model can maximize student learning outcomes and learning objectives will be achieved. This study aims to determine the effect of the Problem Based Learning (PBL) learning model on the learning outcomes of vocational high school students. This research was conducted through a literature review and relevant research results and was continued through a Focus Group Discussion (FGD). From the research it was found that there was a significant positive influence between the problem-based learning (PBL) model variable and student learning outcomes, which meant that student learning outcomes could be improved through the application of the Problem Based Learning (PBL) learning model.